Update der S3-Leitlinie Mammakarzinom: Was gibt es Neues für Pathologen? - Lebeau, Annette; Sinn, Peter (Der Pathologe, 2019)
The relevant content changes for pathologists in the updated interdisciplinary S3 guideline “Early detection, diagnosis, therapy and aftercare of breast cancer” are explained and discussed in the context of the most recent evidence. These include recommendations for risk assessment using Ki-67 and the use of multigene tests in the decision for or against adjuvant chemotherapy in estrogen receptor(ER)‑/progesterone receptor(PR)-positive and human epidermal growth factor receptor 2 (HER2)-negative invasive breast cancer. In addition, the assessment of HER2 status is explained. It is described which threshold distance or resection margin status is considered sufficient for resection of ductal carcinoma in situ (DCIS) and invasive breast carcinoma. Finally, recommendations concerning the clinical consequences to be drawn from the detection of a risk lesion in a core needle or vacuum biopsy or at the resection margin of a breast surgical specimen are discussed.